Experimental induction of Theileria parva lawrencei carrier state in African buffalo (Syncerus caffer) - Grootenhuis, J.G.; Leitch, L.; Stagg, D.A.; Dolan, T.T.; Young, A.S. (Cambridge University Press, 1987)
An African buffalo (Syncerus caffer), born in captivity and demonstrated to be Theileria-free, and 2 susceptible cattle were inoculated with a Theileria parva lawrencei sporozoite stabilate. The buffalo had a very mild disease reaction, while the 2 cattle died of acute theileriosis. It was possible to isolate T. p. lawrencei from the buffalo up to 888 days after infection by the application of non-infected Rhipicephalus appendiculatus nymphs and up to 657 days after infection by the establishment of lymphoblastoid cell lines infected with T. p. lawrencei schizonts from peripheral mononuclear blood cells. The infection rate and levels of Theileria in the resultant adult ticks varied from 11 to 70% with 0·3–11 acini infected/tick. Stabilates prepared from these tick batches caused fatal T. p. lawrencei infections in cattle.